## Are (x+10)+x+9 and 2(x+7)+5 Equivalent?

Let's explore whether the expressions **(x+10)+x+9** and **2(x+7)+5** are equivalent. To determine this, we need to simplify both expressions and see if they result in the same outcome.

### Simplifying the Expressions

**1. (x+10)+x+9**

**Combine like terms:**- x + x = 2x
- 10 + 9 = 19

**Simplified expression:**2x + 19

**2. 2(x+7)+5**

**Distribute the 2:**- 2 * x = 2x
- 2 * 7 = 14

**Combine like terms:**- 14 + 5 = 19

**Simplified expression:**2x + 19

### Conclusion

After simplifying both expressions, we find that they both result in **2x + 19**. Therefore, the expressions **(x+10)+x+9** and **2(x+7)+5** are **equivalent**.